Early Vascular Aging in Normotensive Patients With Systemic Lupus Erythematosus: Comparison With Young Patients Having Hypertension. (August 2016) - Morreale, Massimiliano; Mulè, Giuseppe; Ferrante, Angelo; D'ignoto, Francesco; Cottone, Santina
Connective tissue diseases, like systemic lupus erythematosus (SLE), are associated with early and accelerated atherosclerosis. Recently, the concept of "early vascular aging" (EVA) has been more widely accepted. Aortic stiffness is one of the important markers of EVA. We evaluated EVA and subclinical atherosclerosis, by measuring aortic pulse wave velocity (aPWV) and carotid intima–media thickness (cIMT), in 50 normotensive patients with SLE (mean age: 39 ± 12 years). We compared these participants with 50 age- and sex-matched patients with essential hypertension (EH) and 20 healthy controls. Each participant underwent 24-hour ambulatory blood pressure monitoring (ABPM), aPWV, and cIMT measurements. Clinic and 24-hour ABPM values were significantly lower in patients with SLE and controls when compared with the participants having EH (all P < .0001), but aPWV and cIMT were significantly lower in the control group when compared with patients having SLE and EH (all P < .001). Overall, patients with SLE and EH had similar cIMT and aPWV values ( P = .31 and P = .47, respectively). Our results suggest that SLE has a similar deleterious impact on EVA as EH.